How the hippocampus preserves order: the role of prediction and context - Davachi, Lila (Trends Cogn Sci, 2015)
Remembering the sequence of events is critical for deriving meaning from our experiences and guiding behavior. Prior investigations into the function of the human hippocampus have focused on its more general role in associative binding, but recent work has focused on understanding its specific role in encoding and preserving the temporal order of experiences. In this review, we summarize recent work in humans examining hippocampal contributions to sequence learning. We distinguish the learning of sequential relationships through repetition from the rapid, episodic acquisition of sequential associations. Together, this research begins to clarify the link between hippocampal representations and the preservation of the order of events.